Facile Single Step Electrochemical Growth of Ni3P on Carbon Cloth for Highly Efficient Hydrogen Evolution Reaction. Issue 6 (1st June 2022) - Das, Manisha; Khan, Zubair Bashir; Kamboj, Navpreet; Banerjee, Manami; Dey, Ramendra Sundar
Abstract : The exploration of facile synthesis, a highly active and cost-effective noble metal-free durable electrocatalyst for hydrogen production through water electrolysis is an essential job in the arena of sustainable and clean energy production. In this context, it is crucially desired to look for an inexpensive noble metal-free electrocatalyst for practical use. In recent studies, nickel phosphides are the widely investigated hydrogen evolution reaction (HER) electrocatalysts owing to their extraordinary electronic properties, corrosion-resistant ability and superior electrocatalytic response. In this study, a highly ordered single-phase Ni3 P is grown on activated carbon cloth (CC*) via a one-step electrochemical deposition method, which offers a facile synthesis route for the development of a highly durable electrocatalyst active towards HER. The hierarchical porous structure of Ni3 P provides effluent ion dynamic channels that encourage expeditious kinetics, superior activity and extraordinary stability. The resulting electrocatalyst (Ni3 P@CC*) shows astonishing electrochemical activity towards HER under alkaline conditions and delivers an overpotential of 150 mV at a current density of 10 mA cm −2 with high durability and large electrochemically active surface area (ECSA) that favours the large-scale hydrogen production for future energy systems.